Solve this system algebraically. 9x + 2y = 5 y - 2x + 3 = 0

The solutions for the systems 9x + 2y = 5, y - 2x + 3 = 0 are x = 11/13, y = -17/13.
Substitute y = 2x - 3 to 9x + 2y = 5:
9x + 2(2x - 3) = 5
9x + 4x - 6 = 5
13x - 6 = 5
13x = 5 + 6
13x = 11
x = 11/13
Solve for y using x = 11/13:
9x + 2y = 5
9(11/13) + 2y = 5
99/13 + 2y = 5
2y = 5 - 99/13
2y = -34/13
y = (-34/13)/(2)
y = -34/26 = -17/13

s

Question

Asked 9/28/2014 1:09:19 PM

Updated 9/29/2014 6:54:23 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [9/29/2014 6:54:22 AM], Confirmed by andrewpallarca [9/29/2014 6:54:23 AM]

Rating

There are no new answers.

Solve this system algebraically. 9x + 2y = 5 y - 2x + 3 = 0 **Weegy:** The solution for 2x+y-10=0, x - y - 4 = 0 is x = 14/3 ,y = 2/3. From 2x + y - 10 = 0 ,we can get y = 10-2x put y= 10 - 2x into the 2th equation x - y - 4 = 0 x -(10 -2x) - 4 = 0 3x = 14 x =14/3 y= 10 -2x y= 10 - 2*14/3 y= 2/3 (More)

Question

Updated 9/29/2014 4:05:14 AM

1 Answer/Comment

The solutions for 9x + 2y = 5, y - 2x + 3 = 0 are x = 11/13, y = -17/13

Multiply -2x + y = -3 by -2:

4x - 2y = 6;

Add two equations:

(9x + 2y = 5) + (4x - 2y = 6):

13x = 11; x = 11/13;

Solve for y:

9x + 2y = 5;

9(11/13) + 2y = 5;

99/13 + 2y = 5;

2y = 5 - 99/13;

2y = -34/13;

y = (-34/13)/2;

y = -34/26 = -17/13

Multiply -2x + y = -3 by -2:

4x - 2y = 6;

Add two equations:

(9x + 2y = 5) + (4x - 2y = 6):

13x = 11; x = 11/13;

Solve for y:

9x + 2y = 5;

9(11/13) + 2y = 5;

99/13 + 2y = 5;

2y = 5 - 99/13;

2y = -34/13;

y = (-34/13)/2;

y = -34/26 = -17/13

Added 9/29/2014 4:05:12 AM

This answer has been confirmed as correct and helpful.

Listening has different purposes. True False **Weegy:** Listening has different purposes. TRUE. (More)

Question

Expert Answered

Updated 9/28/2014 1:11:07 PM

0 Answers/Comments

Solve this system algebraically. 7x - 2y = 4 5y + 3x = 10 **Weegy:** i am sorry but is not working to copy and paste all signs so please follow the link and you will see the entire solution, thank you (More)

Question

Updated 9/28/2014 3:37:08 PM

1 Answer/Comment

The solutions for the system 7x - 2y = 4, 5y + 3x = 10 are x = 40/41, y = 58/41

(7x - 2y = 4) * 5:

35x - 10y = 20;

(3x + 5y = 10) * 2:

6x + 10y = 20;

(35x - 10y = 20) + (6x + 10y = 20):

41x = 40;

x = 40/41;

Solve for y:

7x - 2y = 4;

7(40/41) - 2y = 4;

280/41 - 2y = 4;

-2y = 4 - 280/41;

-2y = -116/41;

y = (-116/41)/(-2);

y = 116/82 = 58/41

(7x - 2y = 4) * 5:

35x - 10y = 20;

(3x + 5y = 10) * 2:

6x + 10y = 20;

(35x - 10y = 20) + (6x + 10y = 20):

41x = 40;

x = 40/41;

Solve for y:

7x - 2y = 4;

7(40/41) - 2y = 4;

280/41 - 2y = 4;

-2y = 4 - 280/41;

-2y = -116/41;

y = (-116/41)/(-2);

y = 116/82 = 58/41

Added 9/28/2014 3:36:58 PM

This answer has been confirmed as correct and helpful.

What is the result of adding the system of equations? 2x + y = 4 3x - y = 6 x = 2 x = 10 5x = 10 **Weegy:** The result of adding the system of equations 2x + y = 4, 3x - y = 6 is 5x = 10. (More)

Question

Updated 9/28/2014 3:12:12 PM

0 Answers/Comments

Solve the system algebraically. Check your work. 5x + 2y = 10, 3x + 2y = 6 **Weegy:**
5x + 2y = 10, 3x + 2y = 6;
Multiply 5x + 2y = 10 by 3: 15x + 6y = 30
Multiply 3x + 2y = 6 by 5: 15x + 10y = 30
Subtract: (15x + 10y = 30) - (15x + 6y = 30): 4y = 0
Solve for y: 4y = 0, y = 0/4 = 0
Solve for x using y = 0:
5x + 2y = 10
5x + 2(0) = 10
5x = 10
x = 10/5
x = 2
The solutions for the systems 5x + 2y = 10, 3x + 2y = 6 is x = 2, y = 0.
CHECK:
5x + 2y = 10
5(2) + 0 = 10
10 = 10
3x + 2y = 6
3(2) + 0 = 6
6 = 6
(More)

Question

Updated 9/29/2014 6:42:07 AM

0 Answers/Comments

32,562,301

questions answered

There are no comments.